2014
DOI: 10.2337/db13-1394
|View full text |Cite
|
Sign up to set email alerts
|

PRMT3 Regulates Hepatic Lipogenesis Through Direct Interaction With LXRα

Abstract: Arginine methylation is responsible for diverse biological functions and is mediated by protein arginine methyltransferases (PRMTs). Nonalcoholic fatty liver disease (NAFLD) is accompanied by excessive hepatic lipogenesis via liver X receptor α (LXRα). Thus we examined the pathophysiological role of PRMTs in NAFLD and their relationship with LXRα. In this study, palmitic acid (PA) treatment increased PRMT3, which is correlated with the elevation of hepatic lipogenic proteins. The expression of lipogenic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…(2002). The mice received palm oil to further induce hepatic steatosis and ensure optimal stimulation of PRMT3 translocation to the nucleus (Chisholm et al ., 2003; Go et al ., 2015; Kim et al ., 2015a). To determine the effect of PRMT3 inhibition under these steatosis‐inducing conditions, mice were treated for 4 days with a total of three injections of SGC707 (30 mg·kg −1 ), which was the dose recommended for in vivo usage (Kaniskan et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2002). The mice received palm oil to further induce hepatic steatosis and ensure optimal stimulation of PRMT3 translocation to the nucleus (Chisholm et al ., 2003; Go et al ., 2015; Kim et al ., 2015a). To determine the effect of PRMT3 inhibition under these steatosis‐inducing conditions, mice were treated for 4 days with a total of three injections of SGC707 (30 mg·kg −1 ), which was the dose recommended for in vivo usage (Kaniskan et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al . (2015a) suggested that PRMT3 functions as a selective LXR modulator in vitro . They have shown a specific induction of lipogenic genes via LXR in a PRMT3 overexpression model and reversal of these effects upon PRMT3 silencing and deletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Recently it was shown that in cells treated with palmitic acid or T0901317 (a liver X receptor a (LXRa) agonist) PRMT3 co-localizes with LXRa in the cell nucleus, regulating hepatic lipogenesis. [2] However, this effect appears to be independent of PRMT3 methyltransferase activity. PRMT3 as well as PRMT1 meth-ylate the recombinant mammalian nuclear poly(A)-binding protein (PABPN1) [3] and have been implicated in oculophar-yngeal muscular dystrophy, which is caused by polyalanine expansion in PABPN1.…”
mentioning
confidence: 99%